Triboelectric Nanogenerator Accelerates Highly Efficient Nonviral Direct Conversion and In Vivo Reprogramming of Fibroblasts to Functional Neuronal Cells. Issue 34 (15th June 2016) - Jin, Yoonhee; Seo, Jungmok; Lee, Jung Seung; Shin, Sera; Park, Hyun‐Ji; Min, Sungjin; Cheong, Eunji; Lee, Taeyoon; Cho, Seung‐Woo
Abstract : Triboelectric nanogenerators (TENGs) can be an effective cell reprogramming platform for producing functional neuronal cells for therapeutic applications. Triboelectric stimulation accelerates nonviral direct conversion of functional induced neuronal cells from fibroblasts, increases the conversion efficiency, and induces highly matured neuronal phenotypes with improved electrophysiological functionalities. TENG devices may also be used for biomedical in vivo reprogramming.